(Nf)QÆZIKA (B:s)E (NP)QÆDRU^NIK DLQ (B11 (NKLASU ZAGALXNOOSWÆTNÆH NAW^ALXNIH ZAKLADÆW (B: (NRÆWENX STANDARTU (B/s)E - (NsIROT@K(B, (NwOLODIMIR dMITROWI^(B,s; (NbA[TOWIJ(B, (NwOLODIMIR )QæWANOWI^s)E ((NhARK)QÆW (B:s)E (NsINICQ(B,s, 2011)
(Np)QÆDRU^NIK Z FÆZIKI DLQ (B11 (NKLASU RÆWENX STANDARTU(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (Nf)QÆZIKAs)E -- 11 (NKLASs; (NF)QÆZIKAs)E; (NP)QÆDRU^NIKIs)E; (NELEKTRI^NE POLEs; (NELEKTRI^NIJ STRUMs; (NELEKTROMAGN)QÆTNE POLEs)E; (NMEHAN)QÆ^NÆ KOLIWANNQs)E; (NKOLIWANNQs; (NHWIL)QÆs)E; (NELEKTROMAGN)QÆTNÆ KOLIWANNQs)E; (NKWANTOWA F)QÆZIKAs)E; (NOPTIKAs; (NHWILXOWA OPTIKAs; (NKWANTOWA OPTIKAs; (NATOMNA F)QÆZIKAs)E; (NQDERNA F)QÆZIKAs)E